"Achievement Gap" Language Affects Teachers' Issue Prioritization. (October 2019) - Quinn, David M.; Desruisseaux, Tara-Marie; Nkansah-Amankra, Akua
The term "achievement gap" is regularly used to describe between-group differences in educational outcomes. However, critics of the term argue that it implies the problem is merely one of student performance and may depress support for policies aimed at structural solutions. We hypothesized that the phrase "racial achievement gap" would elicit lower levels of issue prioritization than the phrase "racial inequality in educational outcomes" due to the latter's connotations of social justice. In a randomized survey experiment with a national teacher sample ( N = 1, 549), our hypothesis was confirmed. However, language did not affect teachers' explanations for existing academic outcome disparities.